2019
DOI: 10.1177/1055665619885555
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Upper Airway Assessment in Treacher Collins Syndrome

Abstract: Objectives: The purpose of this investigation was to assess the pharyngeal dimensions and the craniofacial morphology of individuals with Treacher Collins syndrome (TCS) when compared to vertical skeletal class II individuals. It is our hypothesis that the upper airways of individuals with TCS are reduced in view of the skeletal pattern and the maxillomandibular dysmorphologies. Materials and Methods: Cone-beam computed tomography scans of 26 individuals had the pharyngeal volume (V) and minimal cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 32 publications
(51 reference statements)
4
25
0
1
Order By: Relevance
“…In the case of Treacher Collins syndrome, even despite the presence of micrognathia and retrognathia in such patients, no statistically significant difference in UA compared to healthy individuals was found [26].…”
Section: Results Discussionmentioning
confidence: 81%
“…In the case of Treacher Collins syndrome, even despite the presence of micrognathia and retrognathia in such patients, no statistically significant difference in UA compared to healthy individuals was found [26].…”
Section: Results Discussionmentioning
confidence: 81%
“…In line, our preliminary analysis also revealed that maxillary and mandibular projections were significantly altered in TCS individuals (data not shown), which may contribute to the development of airway obstruction secondary to abnormal bony morphology. It has been reported that around 46% of TCS individuals experienced some degree of airway obstruction, 61,62 ranging from mild obliteration to severe and life‐threatening obstructive sleep apnea 63 . Esenlik et al 64 described that increased mandibular retrognathia, decreased posterior facial height, wider maxillary/mandibular plane angle, and wider symphysis notch angle are strongly correlated with TCS severity.…”
Section: Discussionmentioning
confidence: 99%
“…Airway and anesthetic implications: Treacher Collins syndrome (TCS) was firstly reported as a hazard for general anesthesia in 1963 by Edward Ross due to the difficulty in maintaining a free and adequate airway. Several associated mechanisms are the cause, namely mandibular hypoplasia, micrognathia, retrognathia, posterior displacement of the bulky tongue, and the pharyngeal hypoplasia, resulting in a small and narrow retromandibular space [29,30]. The presence of a temporomandibular joint abnormality or a small mouth aperture may further worsen the case.…”
Section: Treacher Collins Syndrome (Tcs)mentioning
confidence: 99%